Reclamation and reuse of graphite from electric vehicle lithium-ion battery anodes via water delamination. Issue 17 (14th April 2023) - Sargent, Alexander T.; Henderson, Zoë; Walton, Alex S.; Spencer, Ben F.; Sweeney, Luke; Flavell, Wendy R.; Anderson, Paul A.; Kendrick, Emma; Slater, Peter R.; Allan, Phoebe K.
Abstract : A simple approach to the delamination of PVDF bound graphite anode material from electric vehicle batteries is presented. This recovered graphite shows good electrochemical performance after a short low temperature thermal treatment. Abstract : Early electric vehicle anodes utilised poly(vinylidene difluoride) (PVDF) as the binder. Due to its lack of solubility in non-harmful solvents, PVDF potentially leads to challenges with anode recycling. In this work we use anodes from discharged and disassembled first-generation end-of-life (EoL) and first-generation quality-control-rejected (QCR) Nissan Leaf cells to demonstrate that PVDF-bound anode active material can be separated from the copper current collector effectively via simple submersion in water. X-ray photoelectron spectroscopy (XPS) and inductively coupled plasma (ICP) spectroscopy were used to confirm the presence of lithiated graphite, suggesting that the delamination process is driven by the reaction of remnant lithiated graphite with water forming H2 which creates localised areas of heat and pressure. The effectiveness of anode delamination via water diminished with the time exposed to air due to the contact with moisture/air slowly hydrolysing and oxidising this lithiated graphite. Electrochemical measurements confirm that annealing the recovered graphite material at 500 °C for 1 h in air to remove solid electrolyte interface layer and PVDF contamination can regenerate material with a performance comparable to commercial graphite. These results suggest that optimised reclamation and regeneration procedures for EoL anodes can provide a source for high performing electrochemical graphite, helping to secure future supplies of this critical raw material and alleviating concerns over future accumulation of battery waste.